Bimodal Bilingualism and the Frequency-Lag Hypothesis - Emmorey, Karen (Oxford University Press, 2013)
The frequency-lag hypothesis proposes that bilinguals have slowed lexical retrieval relative to monolinguals and in their nondominant language relative to their dominant language, particularly for low-frequency words. These effects arise because bilinguals divide their language use between 2 languages and use their nondominant language less frequently. We conducted a picture-naming study with hearing American Sign Language (ASL)–English bilinguals (bimodal bilinguals), deaf signers, and English-speaking monolinguals. As predicted by the frequency-lag hypothesis, bimodal bilinguals were slower, less accurate, and exhibited a larger frequency effect when naming pictures in ASL as compared with English (their dominant language) and as compared with deaf signers. For English there was no difference in naming latencies, error rates, or frequency effects for bimodal bilinguals as compared with monolinguals. Neither age of ASL acquisition nor interpreting experience affected the results; picture-naming accuracy and frequency effects were equivalent for deaf signers and English monolinguals. Larger frequency effects in ASL relative to English for bimodal bilinguals suggests that they are affected by a frequency lag in ASL. The absence of a lag for English could reflect the use of mouthing and/or code-blending, which may shield bimodal bilinguals from the lexical slowing observed for spoken language bilinguals in the dominant language.